(untitled) (Al-Academy, 2023)
Since its inception, the theatrical performance has been based on the principle of permanence, continuity, renewal and innovation in the structure of its visual elements. These innovations and the effectiveness of continuity cannot be achieved without searching for everything that is new and different at the level (form and content) in order to create an image with innovative and effective features in the theatrical discourse, and from Among the elements of the theatrical performance (theatrical costumes) that have been subject to variation since the beginning of the theater until now, and for this purpose, the current research was conducted with the question of the research problem: What are the variations of costumes in the contemporary Iraqi theatrical performance.And (theoretical framework) the first topic: the concept of contrast in theatrical performance, the second topic: the different vision of theatrical currents, the third topic: the differentiation of costumes in form and content, and indicators of the theoretical framework.The (research procedures) came from the research community and the research method: descriptive analytical or research sample (presentation of a play of revelations). The results came as conclusions, recommendations and suggestions, and the most important results are:1- The events in different costumes are subject to the requirements of the idea of the play and its events, and this is what we find evident in all the costumes of theatrical characters (disclosures) in the characters (Al-Hajjaj, Aisha, and the servant).2- Contrasting with costumes does not mean distortion and lack of clarity in their forms, but rather follow steps in design with scientific and applied dimensions that produce a different costume that is comprehensible and understandable. The search concluded with a list of sources